Tax Morality and Progressive Wage Tax - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2010)
We analyze the impact of tax morality on progressive income (wage) taxation. We assume that transfers (cash-back) and public expenditures are financed from linear wage taxes. We derive the reported wages from individual utility maximization, when individuals obtain partial satisfaction from reporting wages (depending on their tax morality), and cannot be excluded from the use of public services. The government maximizes a utilitarian social welfare function, also taking into account the utility of public services. The major conjecture is illustrated by numerical examples: the optimal degree of redistribution and the size of the public services are increasing functions of the individuals' tax morality.
Keywords: H55; D91; 330; tax moral; reporting earnings; progressive income tax; welfare economics; Steuermoral; Lohnsteuer; Wohlfahrtsökonomik